Mengembangkan Potensi Desa dengan Peningkatan Kesehatan dan Kreativitas Masyarakat - Ramon Syahrial (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2019)
Health development aims to increase awareness, willingness and the ability to live healthy for everyone in order to realize the highest degree of public health, as an investment for the development of productive human resources socially and economically. The community service program was carried out in the village of Bendungan, Kelurahan Sumur Welut, Lakarsantri District, Surabaya. The objectives are (1) Increasing public awareness of health, In Bendungan Village, the majority of the people are farmers. They often do not care about their health condition, this is proven if there is no pain, it does not need to be examined for their health. (2) Creating a creative society so that they are able to innovate with resources, (3) make Bendungan village one of the tourist destinations that aims to improve the economy and welfare.In this case, so that the program plan can be implemented and sustainable, it must optimize the resources available in Bendungan village by involving the community. So that the planned program is faster implemented. Health programs are carried out on a scheduled basis by conducting socialization regarding health and the importance of health, while the creativity program is carried out by providing training and skills that support the village's potential.